الفحص الضريبي على الدخل لتحقيق وعاء مقبول في ضوء تمسك المكلفين بحساباتهم: دراسة تطبيقية في الهيئة العامة للضرائب (Journal of Accounting and Financial Studies ( JAFS ), 2011)
Examination is a form of tax audits which have been done by tax examiner rests with the General Commission for Taxes is responsible for determining the extent to which the amounts subject to  tax provided  by  the holders of admissions with  the laws and regulations, taxes. So the tax-examination is the major means of tax administration to make sure the fact that tax revenues generated from the imposition of taxes different kinds of direct and indirect search result, the importance of the role played by the (Department of Control and Internal Audit / Audit Division in charge) in charge of auditing the accounts, which may be Maclvoha clung to their accounts and access to the tax base acceptable to the expensive and financial authority in the event of a discrepancy in the calculation of the tax.     The aim of this research is to achieve a set of goals that a most important use of the tax examination of the accounts in charge at the lack of agreement between the taxpayer and financial authority and the final presentation of the accounts to ensure that the two parties can achieve justice examining the accounts of the taxpayer and protect the rights of the public treasury.